Literature Review: The Relationship Between Procrastination and Academic Stress - Haikal, Muhammad; Sugiono, Muhammad Rafly Adrian; Azzahra, Anis Aura; Fauzan, Naufal Revaldy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Academic procrastination and academic stress represent two interrelated issues frequently encountered by university students and have been shown to adversely affect academic performance as well as psychological well-being. This literature review synthesizes current evidence regarding the conceptualization, contributing factors, and consequences of academic procrastination, while also examining the mechanisms through which academic stress influences procrastinatory behavior. Internal factors such as limited motivation, inadequate time-management abilities, insufficient understanding of academic tasks, and psychological and physical fatigue were identified as key determinants of procrastination. External factors, including heavy academic workloads, unclear instructions, peer influence, and inconsistent assignment deadlines, further intensify procrastinatory tendencies. Academic stress, defined as the condition in which academic demands exceed an individual's adaptive capacity, is associated with anxiety, sleep disturbances, changes in nutritional patterns, reduced concentration, and other physiological or emotional consequences. Evidence from multiple empirical studies indicates a positive and reciprocal association between academic procrastination and academic stress, suggesting that elevated stress levels increase procrastination, while procrastination, in turn, heightens stress. This reinforcing cycle underscores the need for targeted interventions. Recommended strategies include segmenting complex tasks into smaller components, reducing feelings of overload, managing perfectionistic tendencies, monitoring daily behavioral patterns, and employing self-reward systems. Overall, a comprehensive understanding of the interplay between academic stress and procrastination is essential for developing effective academic and psychological support strategies for students.